2020
DOI: 10.1016/j.annonc.2020.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Trifluridine/tipiracil plus bevacizumab in patients with untreated metastatic colorectal cancer ineligible for intensive therapy: the randomized TASCO1 study

Abstract: Background:We designed an open-label, noncomparative phase II study to assess the safety and efficacy of first-line treatment with trifluridine/tipiracil plus bevacizumab (TTeB) and capecitabine plus bevacizumab (CeB) in untreated patients with unresectable metastatic colorectal cancer (mCRC) who were not candidates for combination with cytotoxic chemotherapies. Patients and methods: From 29 April 2016 to 29 March 2017, 153 patients were randomly assigned (1:1) to either TTeB (N ¼ 77) or CeB (N ¼ 76). The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 17 publications
6
41
0
Order By: Relevance
“…For example, a Phase III trial (SOLSTICE) is currently investigating the efficacy and safety of FTD/TPI plus bevacizumab (versus capecitabine plus bevacizumab) in the first-line treatment of mCRC in patients who are not eligible for intensive chemotherapy [28]. This trial follows on from the Phase II TASCO1 trial, in which FTD/TPI plus bevacizumab showed promising activity in this patient group (median PFS and OS: 9.2 and 18 months, respectively) [29]. Although the efficacy results of SOLSTICE will not inform the third-line treatment of mCRC, it will generate safety and tolerability data that may facilitate decision-making across the continuum of care.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…For example, a Phase III trial (SOLSTICE) is currently investigating the efficacy and safety of FTD/TPI plus bevacizumab (versus capecitabine plus bevacizumab) in the first-line treatment of mCRC in patients who are not eligible for intensive chemotherapy [28]. This trial follows on from the Phase II TASCO1 trial, in which FTD/TPI plus bevacizumab showed promising activity in this patient group (median PFS and OS: 9.2 and 18 months, respectively) [29]. Although the efficacy results of SOLSTICE will not inform the third-line treatment of mCRC, it will generate safety and tolerability data that may facilitate decision-making across the continuum of care.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Importantly, the improvement in OS will be a key consideration by funding agencies. Its role in earlier lines of treatment remains to be answered by ongoing trials [ 19 , 20 , 21 ]. Our study suggests some tumour-factors that may help select patients who would most benefit from Lonsurf.…”
Section: Discussionmentioning
confidence: 99%
“…The TASCO1 study is a phase II randomised open-label noncomparative study assessing safety and efficacy (PFS, primary outcome) of first-line treatment with trifluridine/tipiracil plus bevacizumab (TT-B) and capecitabine plus bevacizumab (C-B) in untreated patients with mCRC not candidates for standard oxaliplatin- or irinotecan-based chemotherapy regimens. Median PFS was 9.2 (95% CI, 7.6–11.6) and 7.8 (95% CI, 5.5–10.1) months in the TT-B and C-B groups, respectively [ 49 ]. At ASCO-GI 2021, authors presented the median OS which was 22.31 months in TT-B and 17.67 months in C-B with HR 0.78 (95% CI, 0.5–1.10).…”
Section: Highlights In Metastatic Colorectal Cancermentioning
confidence: 99%